Monochrome and colour television - Gulati, R. R. (New Age International, 2005)
About the Book: This text is based on the CCIR 625-B monochrome (black & white) and the compatible PAL-B colour television standards as adopted by India and many other countries. The American NTSC and French SECAM television systems have also been accorded due coverage while presenting various aspects of the subject starting from TV camera to the receiving picture tube. While this book was published soon after television was introduced in India it continues to be very useful as a comprehensive text book because of excellent presentation of the fundamentals and analysis of all aspects of te.